Biphase Cobalt–Manganese Oxide with High Capacity and Rate Performance for Aqueous Sodium‐Ion Electrochemical Energy Storage. (22nd November 2017) - Shan, Xiaoqiang; Charles, Daniel S.; Xu, Wenqian; Feygenson, Mikhail; Su, Dong; Teng, Xiaowei
Abstract: Manganese‐based metal oxide electrode materials are of great importance in electrochemical energy storage for their favorable redox behavior, low cost, and environmental friendliness. However, their storage capacity and cycle life in aqueous Na‐ion electrolytes is not satisfactory. Herein, the development of a biphase cobalt–manganese oxide (CoMnO) nanostructured electrode material is reported, comprised of a layered MnO2 ⋅H2 O birnessite phase and a (Co0.83 Mn0.13 Va0.04 )tetra (Co0.38 Mn1.62 )octa O3.72 (Va: vacancy; tetra: tetrahedral sites; octa: octahedral sites) spinel phase, verified by neutron total scattering and pair distribution function analyses. The biphase CoMnO material demonstrates an excellent storage capacity toward Na‐ions in an aqueous electrolyte (121 mA h g −1 at a scan rate of 1 mV s −1 in the half‐cell and 81 mA h g −1 at a current density of 2 A g −1 after 5000 cycles in full‐cells), as well as high rate performance (57 mA h g −1 a rate of 360 C). Electrokinetic analysis and in situ X‐ray diffraction measurements further confirm that the synergistic interaction between the spinel and layered phases, as well as the vacancy of the tetrahedral sites of spinel phase, contribute to the improved capacity and rate performance of the CoMnO material by facilitating both diffusion‐limited redox and capacitive charge storage processes. Abstract : In situ X‐ray diffraction characterizations of biphase CoMnO material are conducted during electrochemical charge (oxidation) and discharge (reduction) processes, the structure evolution of CoMnO results from Na‐ion intercalation and/or deintercalation for aqueous energy storage and is verified by the variations of the lattice constants or layered spacing of a Co1.21 Mn1.75 O3.72 spinel phase and a MnO2 layered birnessite phase.